Osteocytes support bone metastasis of melanoma cells by CXCL5 - Jia, Yewei; Zhang, Fulin; Meng, Xianyi; Andreev, Darja; Lyu, Pang; Zhang, Wenshuo; Lai, Chaobo; Schett, Georg; Bozec, Aline (Cancer Letters, 2024)
Bone metastasis is a common complication of certain cancers such as melanoma. The spreading of cancer cells into the bone is supported by changes in the bone marrow environment. The specific role of osteocytes in this process is yet to be defined. By RNA-seq and chemokines screening we show that osteocytes release the chemokine CXCL5 when they are exposed to melanoma cells. Osteocytes-mediated CXCL5 secretion enhanced the migratory and invasive behaviour of melanoma cells. When the expression of the CXCL5 receptor, CXCR2, was down-regulated in melanoma cells in vitro, we observed a significant decrease in melanoma cell migration in response to osteocytes. Furthermore, melanoma cells with down-regulated CXCR2 expression showed less bone metastasis and less bone loss in the bone metastasis model in vivo. Furthermore, when simultaneously down-regulating CXCL5 in osteocytes and CXCR2 in melanoma cells, melanoma progression was abrogated in vivo. In summary, these data suggest a significant role of osteocytes in bone metastasis of melanoma, which is mediated through the CXCL5-CXCR2 pathway.
CRIS-Team Scopus Importer:2024-04-26